New technologies in biomedicine. Opinions of young Romanian physicians - Hostiuc, Sorin; Buda, Octavian; Mihailov, Claudia Ileana; Hostiuc, Mihaela (Acta Bioethica, 2015)
The purpose of this article is to summarize the way young medical professionals view these modern biomedical procedures and their moral acceptability. Materials and methods: A survey, filled in online, analyzing items in four main areas: genetic techniques, cloning, stem cell research, and assisted reproduction. Results: Most subjects agreed that the right to the genetic material should be a fundamental human right and that genetic engineering should be used if it could lead to the elimination os severe genetic diseases like cystic fibrosis and thalassemia. The least acceptance rate was obtained for techniques that would either change physical traits (like eye or hair color) or augment them. Most subjects agreed that the prenatal screening should be mandatory, and if the screening detects a severe congenital malformation the physician should recommend therapeutic abortion. Most subjects disagreed that cloning of any type, either therapeutic or reproductive, using human, animal, or vegetal genetic material. Most subjects agreed with the collection and storage of cord blood stem cells and the use of adult stem cells, and most of them disagreed with the creation of embryos specifically for obtaining stem cells. Conclusions: Even if the national legislation in this area is very scarce, the responses have usually identified the highly controversial techniques. If however the national legislation has elements similar to the items from the survey, they tended to take the respective items as morally acceptable without trying to analyze them critically.